Labia minoraplasty - the balance between technique and untoward effects: A case report (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
Case presentation: A 45-year-old nulliparous patient presented with a long-standing history of genitaldiscomfort in the form of friction, laceration, and dyspareunia. She was also esthetically displeased withher labia minora, which she considered too large and long. Her labia minora appearance was also notedto cause emotional distress. The patient requested labia minoraplasty. Despite correct techniqueselection, she was noted to have notching, fenestration, and pigment mismatch eight weekspostoperatively, and required revision surgery.Discussion: Wedge resection versus edge trimming is an active topic in cosmetic gynecology. Patientselection and hypertrophied labia minora are important considerations in technique selection. Thesehave a bearing on the eventual esthetic appearance and development of untoward effects.Conclusion: Even with the correct technique selection for a specific type of labial hypertrophy, untowardeffects may develop postoperatively, requiring reconstruction or revision later.